THE EXISTENCE OF E-MONEY AS A MODERN FINANCIAL EXCHANGE FROM THE PERSPECTIVE OF THE ISLAMIC ECONOMY - Afidah Rozi Anti; Ahmad, Hendri Hermawan Adinugraha (Journal of Islamic Management Studies, 2023)
The rapid development of the times requires humans to be able to adapt to the emergence of new technology. The existence of new technology can help humans work in various fields. One of them is in financial transactions. The phenomenon of e-money as a modern financial technology in digital payments has become a trend that has colored financial and business activities. The purpose of this study is to analyze phenomena in the transformation of financial transactions, contracts in e-money transactions, and an overview of e-money in Islamic economics. This study’s research was conducted using a qualitative literature study methodology. Secondary data is the research’s primary data source. This study employed content analysis or content study to analyze the data. The three steps of the data analysis process are data reduction, data display, and conclusion. The results of this research are that payment instruments have developed rapidly from pre-barter transaction systems to transaction systems using digital money. E-money in the Islamic Economic has now become part of technological advances in society, so is lawful and already complying with the rules of Islamic law as a means of transaction and mullah. This halalness is based on the rules and demands of human needs for electronic money and contemplating the various benefits that are in it.